ENHANCING STUDENTS' CRITICAL THINKING CAPABILITIES IN IPAS GRADE V PRIMARY SCHOOL THROUGH CULTURALLY RESPONSIVE TEACHING - Hartini, Ayu (Four Son Scholarship, 2025)
The purpose of this study was to determine the improvement in students' critical thinking skills through the Culturally Responsive Teaching (CRT) approach in Grade V Science and Mathematics subjects at elementary school. The research method used was classroom action research. The subjects of this study were 10 Grade V students at SDN 1 Kudu Kertosono Nganjuk. The data analysis process in this study was guided by the steps of qualitative research data analysis. These analysis steps consisted of three concurrent activities, namely: (1) data reduction, (2) data presentation, and (3) conclusion drawing.The results of this study indicate that after implementing the Culturally Responsive Teaching (CRT) approach to improve students' critical thinking skills, there was an increase in learning outcomes and student activity, as observed. This can be seen from the observation results, which show that student activity in cycle I was 66%, while in cycle II it was 82.87%. Thus, it means that in cycle II, students' critical thinking skills had increased compared to cycle I. This was also proven by the students' learning outcomes in the pre-intervention test, cycle I and cycle II. The success rate score showed an upward trend, increasing from 70 in the pre-action, to 79 in cycle I, and further increasing to 90.5 in cycle II. Thus, the Culturally Responsive Teaching (CRT) approach can improve students' critical thinking skills.